Auxiliary Biomembranes as a Directional Delivery System To Control Biological Events in Cell-Laden Tissue-Engineering Scaffolds - Knopf-Marques, Helena; Barthes, Julien; Wolfova, Lucie; Vidal, Bérengère; Koenig, Geraldine; Bacharouche, Jalal; Francius, Grégory; Sadam, Helle; Liivas, Urmas; Lavalle, Philippe; Vrana, Nihal Engin (ACS omega, 2017)
Delivery of growth factors is an indispensable part of tissue engineering. Here, we describe a detachable membrane-based release system composed of extracellular matrix components that can be attached to hydrogels to achieve directional release of bioactive molecules. This way, the release of cytokines/growth factors can be started at a desired point of tissue maturation or directly in vivo. As a model, we develop thin films of an interpenetrating network of double-cross-linked gelatin and hyaluronic acid derivatives. The use of the auxiliary release system with vascular endothelial growth factor results in extensive sprouting by encapsulated vascular endothelial cells. The presence of the release system with interleukin-4 results in clustering of encapsulated macrophages with a significant decrease in M1 macrophages (proinflammatory). This system can be used in conjunction with three-dimensional structures as an auxiliary system to control artificial tissue maturation and growth.